2021
DOI: 10.3390/jcm10225373
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Bone Score (TBS) in Patients with Early Ankylosing Spondylitis—Limited Utility

Abstract: Purpose: Ankylosing spondylitis (AS) not only results in pathological ossification of the spine, but can also be associated with osteoporosis. Due to the presence of syndesmophytes and possible involvement of the hip joints, classical dual X-ray absorptiometry (DXA) is of limited use in patients with advanced stages of AS. Trabecular bone score (TBS) is a method complementary to DXA, providing additional information about bone microarchitecture. There is a growing body of evidence for the usefulness of TBS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…To date, the question of what leads to bone mass loss and bone tissue formation, and whether these processes are related to inflammation, remains poorly understood. In previous studies, it was reported that at the beginning of the disease, a decrease in BMD still prevails over osteoproliferative changes [9] and is associated not only with a number of general factors (age, sex, smoking, low body weight, hypogonadism) but also with the direct influence of a persistent inflammatory process, longterm use of glucocorticsteroids (GCs), vitamin D deficiency, decreased motor activity, etc. [3,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the question of what leads to bone mass loss and bone tissue formation, and whether these processes are related to inflammation, remains poorly understood. In previous studies, it was reported that at the beginning of the disease, a decrease in BMD still prevails over osteoproliferative changes [9] and is associated not only with a number of general factors (age, sex, smoking, low body weight, hypogonadism) but also with the direct influence of a persistent inflammatory process, longterm use of glucocorticsteroids (GCs), vitamin D deficiency, decreased motor activity, etc. [3,7,10].…”
Section: Introductionmentioning
confidence: 99%